De la Ley Orgánica de salud sexual y reproductiva e interrupción voluntaria del embarazo al anteproyecto de Ley Orgánica de protección de la vida del concebido y de los derechos de la mujer embarazada: buscando los porqués últimos de la supresión de derechos fundamentales - Jasone Astola Madariaga (Revista Vasca de Administración Pública, 2014)
When we investigated, we often forget that the tools we use have not arisen spontaneously, but that a knowledge/power has built them, and they have passed through our education system That is, in the field of constitutional law, the first thing discussed in this work, with two objectives: To see something that still remains invisible, who and how is the subject on which the constitutional law has been built ¿a man, white, owner and heterosexual¿ and the influence of this pre-decision on all the legal system and in the formation of our personality; and to reveal the impossibility of equality of women and men in a system that has been built like this. All of this to clarify that sexual rights and reproductive rights are pending a thread at this time is simply a direct result of the system itself.